PRESTASI BELAJAR DAN MANAJEMEN WAKTU KULIAH MAHASISWA - Muliyani, Sri Erny (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
A person who has a learning achievement can be proven success through assessment after implementing learning. It is said to have a high learning achievement if able to master the learning that has been accepted during college, and otherwise have a low learning achievement if someone is not able to master the learning that has been received. Time management is one of the factors that can affect learning achievement with the mechanism of making work schedules for all work completed in a timely manner. The purpose of this study is to describe the learning achievement and time management of the Faculty of Sport and Health Education (FPOK) Institute of Teacher Training Education (IKIP) Mataram. Methods of data collection with observation, questionnaires, interviews, and documentation. Data analysis with collection, reduction, display, and conclusions. The results showed that there is a good relationship between student learning achievement with time management ie students make the planning and determine the priority of college to be able to improve the quality and professionalism of students in the future.